(untitled) (Research, Society and Development, 2022)
Objective: To carry out a systematic review, demonstrating the prevention of diseases by consuming anthocyanins. Methodology: A systematic search was carried out on the electronic data platforms Lilacs, PubMed, and ScienceDirect for articles that presented the benefits of anthocyanin consumption for some diseases. The articles included in this review are original in vivo and in vitro. The term used was “anthocyanin” in Portuguese and English, restricting the search in the last 10 years. Review articles were excluded, as well as studies that used foods containing anthocyanin or extracts, as other compounds may be involved. Result: After the exclusion steps, 11 articles were selected, being 8 in vitro and 3 studies carried out in vivo with animals, being these mice. The benefits of anthocyanins in diseases such as atherosclerosis, ischemic disease, endothelial dysfunction; neurodegenerative diseases such as Alzheimer’s disease, neurotoxicity, Huntington’s disease; diseases linked to diabetes such as diabetes mellitus, diabetic cardiomyopathy, as well as cancer diseases; in addition to lung diseases. Conclusion: Studies show that intervention with anthocyanin is effective in preventing and treating the diseases presented since they have benefits when added to the diet, including mechanisms of protection, reduction, cell modulation, and activation of pathways.